2013
DOI: 10.1590/s1519-69842013000200028
|View full text |Cite
|
Sign up to set email alerts
|

The orchid-bee faunas (Hymenoptera: Apidae) of 'Parque Nacional do Monte Pascoal', 'Parque Nacional do Descobrimento' and three other Atlantic Forest remnants in southern Bahia, eastern Brazil

A Nemésio

Abstract: The orchid-bee faunas of 'Parque Nacional do Monte Pascoal', 'Parque Nacional do Descobrimento' and three other Atlantic Forest remnants ranging from 1 to 300 ha in southern Bahia, eastern Brazil, were surveyed. Baits with seventeen different scents were used to attract orchid-bee males. Four thousand seven hundred and sixty-four males belonging to 36 species were actively collected with insect nets during 300 hours from November, 2008 to November, 2009. Richness and diversity of orchid bees found in this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 46 publications
2
11
0
3
Order By: Relevance
“…The orchid bee richness recorded in the Pratigi Environmental Protection Area was similar to that in an area within the Atlantic Forest, in the Serra do Conduru State Park, where 22 species were reported (Nemésio, 2011a); and in the Michelin Ecological Reserve, where 21 species were registered, both localized in the southern Bahia, Brazil (Rosa et al, 2015) However, the species richness found was lower than that reported for the Monte Pascoal National Park, located 360 km away from the Pratigi Environmental Protection Area (36 species) (Nemésio, 2013b). According to Souza et al (2005), variation in of orchid-bee richness can be influenced by differences factors, including in collection method, types of fragrances used and the sampling effort.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The orchid bee richness recorded in the Pratigi Environmental Protection Area was similar to that in an area within the Atlantic Forest, in the Serra do Conduru State Park, where 22 species were reported (Nemésio, 2011a); and in the Michelin Ecological Reserve, where 21 species were registered, both localized in the southern Bahia, Brazil (Rosa et al, 2015) However, the species richness found was lower than that reported for the Monte Pascoal National Park, located 360 km away from the Pratigi Environmental Protection Area (36 species) (Nemésio, 2013b). According to Souza et al (2005), variation in of orchid-bee richness can be influenced by differences factors, including in collection method, types of fragrances used and the sampling effort.…”
Section: Discussionsupporting
confidence: 62%
“…The region is known as an important endemism area for several taxonomic groups, and has been considered one of the most important in the Atlantic Forest (Franke et al, 2005;Nemésio, 2013a). The orchid bee fauna of the Central Atlantic Forest Corridor was studied in the southern portion of Bahia (Nemésio, 2013a;Nemésio, 2013b;Nemésio, 2013c;Nemésio, 2014) and in a region near to our study area (Rosa et al, 2015). However, large variations have been observed in orchid bee communities, even in neighboring regions, which could be related to habitat heterogeneity (Tonhasca et al, 2002b).…”
mentioning
confidence: 99%
“…The protocol proposed by Nemésio (2010b) has already been used in more than twenty areas in northeastern Brazil (Nemésio, 2010b; this study), southern Bahia (Nemésio, 2011a(Nemésio, , 2013a, northern Espírito Santo (Nemésio, 2011b(Nemésio, , 2013b, Minas Gerais (Nemésio, 2012c;Nemésio and Paula, 2013), and the Peruvian Amazon (Nemésio et al, 2014), always with a high number of collected specimens during a relatively short period of time. With more than 3,000 bees collected in only ten days, the present study revealed one of the highest abundances ever recorded with this 20-hour sampling strategy, only rivalled by the regions of Monte Pascoal, in southern Bahia (Nemésio, 2013d), and Linhares, in northern Espírito Santo (Nemésio, 2013b). On the other hand, it must be emphasised that this protocol potentially fails to record the actual richness of species Table 4.…”
Section: Sampling Protocolmentioning
confidence: 58%
“…gaianii Dressler, 1982d, a junior synonym). In the Atlantic Forest it had been recorded in Rio de Janeiro (Tonhasca Junior et al, 2002), Minas Gerais (Nemésio and Silveira, 2006), Espírito Santo (Nemésio, 2011b) and Bahia (Nemésio, 2013d). The present record represents a range extension of over 700 km northwards, but it must be pointed out that specimens belonging to this species have been also collected in the states of Ceará and Piauí, and currently deposited at the Entomological Collection of Universidade Federal de Uberlândia.…”
Section: Euglossa Hemichlora Cockerell 1917mentioning
confidence: 60%
See 1 more Smart Citation